Hearing Our Voices: A Descriptive Process of Using Film for Anti-racist Action in Nursing - Danda, Michelle; Pitcher, Claire; Key, Jessica (Witness: The Canadian Journal of Critical Nursing Discourse, 2022)
Racism in healthcare is real and it impacts nurses in ways that permeate the culture of healthcare. In the context of increasing social discourse about racism in healthcare, a group of nurses in British Columbia, Canada, felt a moral obligation to expose the social injustice of the systemic racism they had witnessed or experienced. They used film, an arts-based medium, as an innovative tool with the potential to reach an array of viewers, for this nurse activist project in anti-racist action. The creative process allowed for a racially diverse group of nurses to engage in meaningful dialogue about racism in healthcare. The purpose of this descriptive methodological article is to describe how a creative team of novice nurse filmmakers used the nursing process as a framework to carry this project from concept to execution. The stages described include the rationale for developing the film, the process of utilizing this as a means of nurse activism, and the value of using film as a strategy for social activism. Film was used to engage nurses and nursing students in anti-racist work that critically challenges the structural racism embedded in healthcare. We request that all readers view our film in conjunction with reading this article to best grasp how this article and the film complement one another because the film and article are intended to co-exist and not to exist in isolation from one another. VIDEO FOUND HERE